Optical solitons in birefringent fibers with the generalized coupled space–time fractional non-linear Schrödinger equations - Fu, Lei; Li, Jingjing; Yang, Hongwei; Dong, Huanhe; Han, Xiaofeng (Frontiers in Physics, 2023)
Solitons can be transmitted over long distances and large capacities in optical fiber communication systems. The nonlinear Schrödinger(NLS) equation is of a great significance nonlinear evolution equation, which is an ideal model to describe optical soliton transmission. In this paper, a family of the generalized coupled space-time fractional NLS equations which describe optical solitons in birefringent fibers are studied by means of semi-inverse and fractional variation method. Various nonlinear forms of the fractional NLS equations including Kerr law, power law, parabolic law, dual-power law and log law are discussed respectively. The exact soliton solutions such as bright, dark and singular solitons are given. Moreover, the behaviors of the obtained solutions are shown by three-dimensional graphics with different fractional orders, which further understand the propagation of the coupled space-time fractional NLS equations in nonlinear optics.